The burden of chronic hepatitis B virus infection in Australia, 2011 - Jennifer H. MacLachlan; Nicole Allard; Vanessa Towell; Benjamin C. Cowie (Elsevier, 2013)
Abstract Objective: The number of Australians living with chronic hepatitis B (CHB) is thought to be increasing, as are adverse outcomes including cirrhosis and liver cancer, however, robust, up‐to‐date estimates of this burden are limited. Contemporary estimates of the prevalence of CHB in Australia are essential to guide appropriate public health and clinical responses. Methods: This study used census‐based methodology attributing risk of CHB by country of birth and Aboriginal and Torres Strait Islander status, augmented with priority risk‐group based estimates. Deterministic mathematical modelling was used for comparison and for validation of census‐derived estimates. Results: An estimated 218,000 Australians (plausible range 192,000-284,000) are living with CHB, a significant increase over previous estimates. The prevalence derived using mathematical modelling was similar, at 204,000. Notable differences were observed by geographic area in both prevalence and the populations predominantly affected. It is estimated that only 56% of people living with CHB in Australia have been diagnosed and notified. Conclusions: The prevalence of CHB in Australia is increasing, with 1% of the population now estimated to be affected. The majority of the burden is experienced by people born overseas in endemic areas, with more than 95% of new cases of CHB entering the population through migration. Implications: It is imperative that more attention and greater resources are devoted to addressing CHB in Australia; to increase the proportion of Australians affected who have been diagnosed and who are on treatment, in accordance with the First National Hepatitis B Strategy.